(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Acquiring knowledge not only leads humanity to goodness, but also to high perfection. In this, first of all, reading books and applying the knowledge they contain serves as one of the main criteria. Based on this, it can be said that the nation’s aspiration for libraries determines its spiritual level.